Reproducibility of echocardiography in assessing left atrial reservoir function in rheumatic mitral valve disease - Mona A Elsaidy; Mohamed A Abdalaal; Ayman A Elsheikh; Sarah Elsharkawi (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2019)
Background: Although abnormal left atrial (LA) reservoir function had been associated with clinical events in patients with mitral valve disease, its routine assessment is not performed due to inaccuracies and difficult time-consuming measurements. Aim: The aim was to study the feasibility and reproducibility of different echocardiographic parameters for LA assessment in patients with rheumatic mitral valve disease. Methods: Two hundred and fifty-nine patients with mitral valve disease underwent full echocardiographic examination. LA reservoir function was measured by two-dimensional (2D) volumes, 3D volumes, and global longitudinal strain (LA GLS). LA GLS, volumes, and total left atrial emptying fraction values were repeated to obtain the intra- and interobserver variabilities. The latter was performed between a nonexpert and two expert examiners. Results: 3D echocardiography was highly feasible in assessing LA function, feasibility was 94%, and was performed in the shortest time (1.3 ± 0.4, ANOVA, P < 0.0001). All LA 3D measurements showed excellent intraobserver and interobserver reproducibility between the two expert readers; coefficient of variation (CV) was 7% and 8%, respectively, for LA maximal volume index (LAVImax). Although CV for interobserver variability between the expert and nonexpert readers was 12% for 3D minimal LAVI (LAVImin), assessment of 2D LA volumes had the lowest reproducibility; CV was 15% for LAVImin. Conclusion: 3-d echocardiography assessment of LA volumes and function in patients with rheumatic heart disease is highly feasible and reproducible; it is easy to learn and can be easily performed by nonexperts.